Accelerating the delivery of justice vs. bureaucratic resistance to reform - Kalliris, Konstantinos; Alysandratos, Theodore (European Liberal Forum, 2017)
The timely and efficient administration of justice is a fundamental aspect of the rule of law and an essential component of any liberal democracy. Delays in the justice system are not uncommon among several EU countries (including Greece), undermining public trust in the rule of law and, through inadequate contract enforcement, economic freedom. Courageous reforms are often needed in order […]